Tinjauan Indeks Massa Tubuh (IMT) Terhadap Verifikasi Geometri pada Teknik 3DCRT Kanker Serviks - Yulideswati, Yulideswati; Nurbaiti, Nurbaiti (CV. Jasa Sukses Abadi, 2024)
The radiotherapy process for cervical cancer patients requires accuracy. Evaluation is usually carried out in the radiotherapy stages, one of which is by verifying geometry. This research was conducted to assess the patient's Body Mass Index (BMI) for geometric verification using the Computed Radiography (CR) portal in the 3DCRT technique with cervical cancer cases at the Radiotherapy Installation at Arifin Achmad Hospital Pekanbaru so that setup variations that occur during the radiotherapy process can be identified. The research design is descriptive qualitative. The author carried out observations and measurements of body mass index (BMI) and assessed the results of geometric setup verification using the Computed Radiography (CR) portal. The research was conducted in September-October 2023. The 17 cervical cancer patients had a Body Mass Index in the fat/obese and thin/skinny categories who took part in the research. The patient data collected is secondary data from the TPS (Treatment Planning System) planning results and verification data from the CR (Computed Radiography) computer. Data were analyzed using simple statistical methods. The results of this research explain differences in the geometric shift in the two Body Mass Index (BMI) groups in the verification process. The shift exceeds the tolerance limit value. Identification of errors that occur during verification becomes input for improving radiotherapy services.